Visitando o museu pela porta dos fundos: vigilantes e transportadores de obras de arte e a ressignificação do habitus - Santos, Bruno Marco Cuer dos [UNIFESP] (2015)
This research aims at investigating the relationship between non-skilled workers and the artistic field through their labor routine among different hiring process: public employees, subcontracted and also those hired directly by the museum. Two specific categories have been selected: museum guards and fine arts road haulers at two of the main museums in São Paulo city: Museum of Modern Art (MAC-SP) and Museum of Contemporary Art of São Paulo University (MAC-USP). We could verify that the labor relationship can indicate differences related to the way that the agents interact within the symbolic universe they are exposed by their labor journey. It is possible to verify ruptures with the habitus as well as certain positions and class representations through future generations opposing, thus, public employees compared to the workers hired by the museum or even those subcontracted. It means that, the stronger employment relationship may generate possibilities of social mobility by the symbolic capital, while the weaker employment relationship might reveal low possibilities of rupture with both: class position and origin.